Kokobe : identité, exclusion et représentation sociale du handicap en Haïti - Henri Claude Télusma (Études Caribéennes)
Names and appellations have always been essential elements in the construction of individual and social identity. They not only convey information about the person to whom they refer, but they also carry cultural, social and sometimes discriminatory meanings. Thus, the name or appellation that is attributed to a person can reveal much more than a simple identification. It can reflect stereotypes, social judgments and influence the perception of others in relation to the individual. This is particularly true when it comes to people with disabilities, whose designations can have profound repercussions on their social integration and their representation in society. In this context, this article focuses on the names attributed to people with reduced mobility in Haiti, and more specifically on the term kokobe, often used to designate people with disabilities in certain regions of the country. This designation, through its history and its current use, allows us to reflect on the impact of designations on the social representation of disabled individuals in Haiti.